The verification of constant preparation methodology for IMCORE code - Galchenko, V.V.; Shlapak, I.I.; Gulik, V.I.; Budik, D.V. (Вопросы атомной науки и техники, 2018)
For fuel loading maintenance at Ukrainian nuclear power units, as well as to ensure the reactor unit economical and safe operation, it is necessary to have accurate and timely information on the energy release fields, temperature distributions and other thermal and nuclear parameters inside core. This task is performed by the in-core control systems, which usually include sensors, communication lines, electronic measuring equipment, as well as computers, algorithms and programs for processing the received information [1]. To date, in Ukraine In-Core Monitoring System’s (ICMS) with three different neutron-physics calculation subsystem (NPCS) are exploited. They are ICMS’s based on “Khortytsya”, “Voyage” and “Beacon”. Each system has both advantages and disadvantages that occur during the exploitation. Therefore, the study of methods for solving the reactor equation, methods for preparing constant software for neutron-physical calculation module is an urgent task to improve the algorithms for determining the energy release fields in the reactor core. In PJSC «SRPA “Impulse” a working group was created to implement such studies. The paper describes the ImCore code for power distribution calculation. The constant software for ImCore preparation methods analysis and some results of comparison between the fields and the operational data are given. Для супроводження паливних завантажень на українських атомних енергоблоках, а також для забезпечення економічної та безпечної експлуатації реакторної установки необхідна наявність точної та оперативної інформації про розподіл полів енерговиділення, температури та інших теплотехнічних і ядернофізичних параметрів всередині активної зони. Це завдання виконують системи внутрішнього реакторного контролю (СВРК), до складу яких у загальному випадку входять датчики, лінії зв'язку, електронна вимірювальна апаратура, а також ЕОМ, алгоритми і програми для обробки отриманої інформації. На базі ПрАТ «СНВО «Імпульс» створена робоча група для реалізації проекту СВРК-М2, в якому в якості підсистеми фізичного розрахунку використовуються українські розробки програмних продуктів для розрахунку і відновлення поля енерговиділення в активній зоні реактора. У роботі представлено опис розрахункового модуля для розрахунку і відновлення поля енерговиділення програмного комплексу ImCore. Наведено аналіз методик підготовки константного забезпечення для ImCore, а також деякі результати порівняння полів з експлуатаційними даними. Для сопровождения топливных загрузок на украинских атомных энергоблоках, а также для обеспечения экономичной и безопасной эксплуатации реакторной установки необходимо наличие точной и оперативной информации о распределении полей энерговыделения, температуры и других теплотехнических и ядернофизических параметров внутри активной зоны. Эту задачу выполняют системы внутриреакторного контроля (СВРК), в состав которых в общем случае входят датчики, линии связи, электронная измерительная аппаратура, а также ЭВМ, алгоритмы и программы для обработки полученной информации. На базе ЧАО «СНПО «Импульс» создана рабочая группа для реализации проекта СВРК-М2, в котором в качестве подсистемы физического расчета используются украинские разработки программных продуктов для расчета и восстановления поля энерговыделения в активной зоне реактора. В работе представлено описание расчетного модуля для расчета и восстановления поля энерговыделения программного комплекса ImCore. Приведен анализ методик подготовки константного обеспечения для ImCore, а также некоторые результаты сравнения полей с эксплуатационными данными.